New observational evidence for a positive cloud feedback that amplifies the Atlantic Multidecadal Oscillation - Bellomo K.; Clement A. C.; Murphy L. N.; Polvani L. M.; Cane M. A. (Geophysical Research Letters, 2016)
The Atlantic Multidecadal Oscillation (AMO) affects climate variability in the North Atlantic basin and adjacent continents with potential societal impacts. Previous studies based on model simulations and short-term satellite retrievals hypothesized an important role for cloud radiative forcing in modulating the persistence of the AMO in the tropics, but this mechanism remains to be tested with long-term observational records. Here we analyze data sets that span multiple decades and present new observational evidence for a positive feedback between total cloud amount, sea surface temperature (SST), and atmospheric circulation that can strengthen the persistence and amplitude of the tropical branch of the AMO. In addition, we estimate cloud amount feedback from observations and quantify its impact on SST with idealized modeling experiments. From these experiments we conclude that cloud feedbacks can account for 10% to 31% of the observed SST anomalies associated with the AMO over the tropics.